Conscienstiousness And Agreeableness In The Context Of Information Variability: Does Leniency Still Exist? ( An Experimental Study of Lecturers in Ambon State of Polytechnic, Indonesia) - et. al., Audry Leiwakabessy , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cognitive Dissonance Theory (CDT) has been employed to analyze the behavioral issues in the performance evaluation for a long decade. However, using Cognitive Dissonance Theory (CDT) to explain the evaluation performance process is still rarely conducted. By applying the Cognitive Dissonance Theory (CDT), this study investigates the influences of information variability and evaluators’ traits (conscientiousness and agreeableness) on the tendency to provide a lower rating. This study involved fifty-two lecturers of the Accounting Department and Business Administration at the Ambon State of Polytechnic to participate in the experiment as a subjects. The research method used an experimental approach which is modified by Bol and Smith, 2011. The results showed that the evaluators tend to increase the rating on lower performance as the information variability increased. However, such a result is not in line with our expectation that more conscientiousness evaluators would provide a lower rating, while more agreeable evaluators would perform the other way around. The research findings recommend the company to create more inflexible subjective measurement procedures to reduce the tendency of lowering the rating, and take into account a certain person to be an evaluator and also to completely this issues and by adding cultural differences aspect could be more interesting.